Bridging gaps at key intersections: Strategies to improve early intervention and treatment access for eating disorders - Juliane Kennett; Henry T. Stelfox (Mental Health Science)
ABSTRACT Mental health is at the forefront of discussions in healthcare, education, and social settings, yet eating disorders remain poorly understood and inadequately treated. This paper presents evidence on risk factors for insufficient recognition and intervention for eating disorders across clinical and community healthcare settings and proposes actionable strategies to improve awareness and early intervention for eating disorders. Specifically, gaps in eating disorder awareness and treatment access are exacerbated at two key intersections within health and social systems. First, eating disorders manifest themselves at the intersection of mental and physical categories of health, which places them at risk of being misunderstood, poorly diagnosed, and insufficiently intervened upon. Second, the peak onset of eating disorders falls at the intersection of adolescence and young adulthood, which is a period of rapid developmental, social change, and transitions in care. This analysis highlights how systemic issues within existing social and health systems underlie these intersections and contribute to the continued stigmatization and inadequate treatment access for eating disorders. Given their increased incidence and severity, there is an urgent need to address both the individual and societal burden of these disorders. Healthcare systems must prioritize coordination between physical and mental health practices and improve transitions in care from pediatric and adult healthcare services. Identifying gaps at intersections provides the opportunity to make concrete progress toward improving awareness and treatment.